Families of students with exceptionalities: a phenomenological study of the lived experiences of families and public school discipline - George, Emily (My University, 2025)
In this study, I explored the lived experiences of eleven Kansas families navigating special education systems and disciplinary practices in public schools. I used a hermeneutic framework to interpret the meanings families ascribe to their advocacy, challenges, and resilience. Participants were limited to families of students with documented disabilities or exceptionalities who were enrolled in and received discipline from a Kansas public middle or high school. I collected data through semi-structured interviews in person and over Zoom and kept a researcher’s journal of my thoughts and responses during the entire research process. I cleaned the transcripts of the interviews and analyzed them using grounded theory approaches informed by Charmaz’s (2025) methodological guidance. I combed the transcripts twice to find recurring ideas, which I grouped into seven themes. Then, I read through the transcripts two more times to search for quotes that highlighted those themes and to check for outliers or discrepancies in my findings. Those findings revealed seven central themes: accessing services or supports, discipline and its effects on student wellbeing, family and school staff relationships, parental advocacy and agency, inequity and bias, familial strain, and informal growth and supports. All participant families described accessing services as a prolonged and continuous process that could be emotionally and financially exhausting. Inequity and systemic bias appeared in surprising ways, such as school staff using overt racial or ableist remarks or with academic performance used to deny formal services or accommodations and to perpetuate misinformation about child development. School staff used informal and formal discipline to promote safety and to discourage undesired behaviors. However, when discipline was exclusionary, it was stigmatizing and reinforced negative student self-perception, often increasing the behaviors the school attempted to decrease. Families reported behaviors being interpreted negatively, rather than being seen as communication or evidence of a skill deficit or underlying need. Teacher relationships emerged as pivotal: supportive educators were transformative influences that anchored the students in schooling, while punitive, traumatizing, or dismissive educators increased student disengagement, distrust of school staff, social isolation, and stress. Parental advocacy was a lifeline for student success, but also a burden, which left parents feeling misunderstood or marginalized. For some families, inequity and bias shaped daily school interactions, with race, disability, previous interactions with the district, academic standing, and narrow eligibility criteria influencing access to services and disciplinary outcomes. These systemic challenges encroached on the home and impacted family stress and dynamics, yet families also highlighted resilience and growth for their students through informal supports and affirming spaces, especially those within extracurricular activities. This study contributes to scholarship on family experiences in special education and public-school discipline through parent and student voices. The findings underscore the impact of school staff responses to and perceptions of students and the deleterious effects on student wellbeing when these are negative or punitive. While the participants mostly communicated neutral or negative experiences, the study findings also emphasize the transformative potential of supportive relationships. Implications for changes in practice include the need for consistent, individualized supports, trauma-informed and restorative disciplinary approaches, supported family-school partnerships, and an overall deeper understanding of students’, and their families’, experiences. In the conclusion, I recommend changes in school policy that highlight the importance of upholding the mandates of IDEA (Individuals with Disabilities Education Act, 2004), addressing the effects of exclusionary discipline, increasing access to information and supports, and strengthening the school-family-student relationship, especially for those students in need of support, such as those for whom the school issues a disciplinary action and those with disabilities or exceptionalities. Ultimately, this study calls for educational systems to move beyond deficit-based perceptions and toward practices that affirm the strengths and individuality of all students and their families.
Keywords: Phenomenology; Students with exceptionalities; School-family relationship; Public school discipline; Special education